The Korean journal of defense analysis
As one of the five SSCI-registered English journals on political sciences in the Asia region, The Korean Journal of Defense Analysis (KJDA) provides an arena for sharing initiatives and new perspectives on defense and security issues of the Asia-Pacific region. To better support this idea of active intercommunication amongst scholars and experts around the globe, the KJDA Editorial Board welcomes the submission of relevant articles and conference reports on all politico-security issues pertaining to the Asia-Pacific region.